Mobility in Ancient Egypt from the shape and strength of the femurs - Jesús, Herrerín; Margarita, Carmenate (Anthropological Review, 2021)
The aim of the study was to establish the degree of robustness and to infer the level of mobility of a group from ancient Thebes (Middle Egypt). Seventy-one left femurs of adult individuals from the 1st century AD from the tomb of Monthemhat (Luxor) were studied.  Metrical, non-metrical variables, shape and size indices of femur were considered. Stature, body mass and Body Mass Index were calculated. All variables showed higher values in males, the vertical diameter of the femoral head was the variable with the highest sexual dimorphism. Non-metric variables also indicated low robustness, with heterogeneous sex distribution. The robustness, pilastric and platymeric indices indicated that the values were close to those of gracile populations in both sexes. Subtrochanteric size and shape showed no sexual dimorphism. The robustness, size and shape in the middle of the diaphysis suggested a mobility related to a daily occupation without intense physical activity in the legs. The results indicate a profile of low robustness, relative sedentarism with apparent sexual division in daily activities.